Role of patient and public participation in health technology assessment and coverage decisions. (February 2011) - Menon, Devidas; Stafinski, Tania
Health technology assessment (HTA) has become an integral part of decision-making on the coverage of new health technologies in most health systems in the developed world. In recent years, pressure to involve patients and members of the public in HTA has grown. In this article, we summarize findings from peer-reviewed and ''gray'' literature, and discussions with key informants to determine potential roles for patients and the public in HTA and coverage decision-making. We also summarize existing roles for both groups in jurisdictions. Although there appears to be a general view that involvement of patients and the public is highly desirable, research offering insights into the effectiveness of different approaches to accomplish this is scarce. Nonetheless, many of the HTA agencies in developed countries have established some mechanism for seeking input from patients or the public in their processes.